2000
DOI: 10.1097/00005392-200003000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Patient Self-Reporting Questionnaire on Impotence, Incontinence and Stricture After Radical Prostatectomy

Abstract: Although radical prostatectomy morbidity is common and affects self-reported overall quality of life, most patients would elect the same treatment again. Impotence and post-prostatectomy incontinence were significantly associated with sexual function satisfaction, quality of life and willingness to undergo treatment again. Bladder neck contracture and/or urethral stricture was associated with willingness to undergo treatment again after adjusting for demographic variables and time from surgery to the survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 19 publications
2
53
0
11
Order By: Relevance
“…Prior studies that have reported results on the association between bowel symptoms and quality of life have not examined the impact across such a wide range of domains. 3,11,17 Using a single question (After your prostate carcinoma treatment, do you feel your overall quality of life is: better than before/same as before/worse than before? ), Kao and colleagues 3 found that incontinence and impotence were significant predictors of overall health status (OR, 0.41 and 0.34, respectively for better or same vs. worse).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies that have reported results on the association between bowel symptoms and quality of life have not examined the impact across such a wide range of domains. 3,11,17 Using a single question (After your prostate carcinoma treatment, do you feel your overall quality of life is: better than before/same as before/worse than before? ), Kao and colleagues 3 found that incontinence and impotence were significant predictors of overall health status (OR, 0.41 and 0.34, respectively for better or same vs. worse).…”
Section: Discussionmentioning
confidence: 99%
“…3,11,17 Using a single question (After your prostate carcinoma treatment, do you feel your overall quality of life is: better than before/same as before/worse than before? ), Kao and colleagues 3 found that incontinence and impotence were significant predictors of overall health status (OR, 0.41 and 0.34, respectively for better or same vs. worse). However, no further detail was gathered on the specific domains of quality of life affected in this retrospective study of prostatectomy patients treated at one of five military hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations